Analisis Sistem Administrasi Dan Keuangan Pada PERUM BULOG Kantor Cabang Batam - Kamaruzaman Kamaruzaman; Sudanto Sudanto; Meti Febriana (Universitas 45 Surabaya, 2023)
Public Company (PERUM) BULOG is a food institution or company that implements and supports government program policies in the field of economy and national development in general, especially in the field of food logistics and optimizing the use of company resources. The research objective was to analyze the administrative and financial systems that run at PERUM BULOG Batam Branch Office. The research uses a qualitative descriptive approach, namely presenting the results of the analysis found on administration and finance at PERUM BULOG KC Batam. Data collection by interviews, observation and documentation of respondents and data sources analyzed. The results of the analysis show that administrative and financial activities at PERUM BULOG Batam Branch Office consist of Depositing the Sales of Medium Rice / KPSH; Confirming Payment and Transferring Sales Proceeds to Sales Orders (SO) KPSH; Confirming Payment and Transferring Sales Proceeds to Commercial Sales Orders (SO); ; Treasury Monitoring Sales Administration Application; Invoice Sheet for Settlement of Sales Proceeds; Checks to be cashed; and File Archive Storage Cabinets. In the end, the role of the design of the financial administration system can help avoid mistakes. Making work more precise, fast and accurate so as to increase effectiveness and productivity.